Volleyball Athletes Training Program Towards Their Achievements - Jolo, Mark Ulysses (International Journal of Multidisciplinary Sciences, 2024)
Sports coaching has changed significantly over the years with a focus on training programs. This study explores the training programs towards the achievement of the athletes that helps to provide inputs in remodeling the training program. This is anchored to Skills Acquisition Theory that incorporates the notion of learning that ranges from cognitive to psychomotor skills.  The researcher employed a quantitative descripted method and the respondents were chosen purposively which composed of volleyball players in one learning institution. A validated survey type questionnaire from three field experts and pilot testing was utilized to gather structured data. The results revealed. The results of the level of athletes training program in particular to physical fitness program, physical literacy program, safety injury prevention program, and health and wellness program and achievement with regards to award and recognition in Volleyball is highly acceptable as perceived by the respondents. Likewise, this study demonstrates the strong link between different training programs and athlete achievements. Furthermore, the statistics show a strong positive correlation between every coaching style and award and recognition received by athletes, demonstrating the pivotal importance coaching ideologies play in promoting athlete success. These results highlight how, in order to maximize athlete accomplishment, coaches and sports organizations may customize training programs based on particular coaching styles. These findings suggest that training programs may be tailored to fit specific coaching styles. Furthermore, knowing how strongly coaching styles and athlete achievements correlate can help allocate resources for training and coaching programs more effectively.